Designing a SETS-based biology teaching module: Efforts to enhance students’ critical thinking and problem-solving skills - Jumiah, Jumiah; Ahda, Yuni; Fransisca, Rozalia (Jurnal Biolokus : Jurnal Penelitian Pendidikan Biologi dan Biologi, 2024)
Based on the problem analysis, 10th-grade students at SMAN 1 Talawi show low critical thinking and problem-solving skills. This research aims to determine the level of validity, practicality, and effectiveness of developing biology teaching modules based on the SETS model to enhance students' critical thinking and problem-solving abilities. The type of research used is research and development with the Plomp model. The research data were analyzed using a Likert scale and t-test. The research results show that the biology teaching module based on the Science, Environment, Technology, and Society (SETS) model has a validity score of 87.91%, with very valid criteria. The practicality assessment shows a score of 84.52% with a very practical criterion. The average score for the critical thinking ability test is 83.85, and the average score for the problem-solving ability test is 83.00. These scores indicate that the effectiveness assessment falls into the high criterion with a very effective interpretation. The results of the t-test show that the P-value < α, so the alternative hypothesis (H1) is accepted. So, it can be concluded that the biology teaching module based on the SETS model that has been developed falls into the category of very valid, very practical, and very effective for enhancing the critical thinking and problem-solving abilities of tenth-grade students. The use of technology in this module is one of the novel aspects, where students are involved in exploring and analyzing issues about ecosystems and environmental changes through technology.